The seductive allure effect extends from neuroscientific to psychoanalytic explanations among Turkish medical students: preliminary implications of biased scientific reasoning within the context of medical and psychiatric training - SAYAR, MUSTAFA KEMAL; YORGUNER, NEŞE; GÜRSOY, SÜHA CAN (Taylor and Francis Ltd., 2022)
Research suggests that people tend to overweight arguments accompanied by neuroscientific terminology, which is dubbed as the seductive allure of neuroscience explanations (SANE) in the literature. Such an effect might be of particular significance when it comes to physicians and mental health professionals (MHP), given that it has the potential to cause significant bias in their understanding as well as their treatment approaches toward psychiatric symptoms. In this study, we aimed to test the SANE effect among Turkish medical students, and assess its uniqueness by comparing it with a discipline that still maintains an important role in contemporary psychiatric training in Turkey: psychoanalysis. 109 medical students with a basic level of knowledge of psychiatry and clinical neuroscience were asked to rate the credibility of explanations of differing quality (good vs. circular) for psychological phenomena, followed by three types of information: none, neuroscientific (SNI) or psychoanalytical (SPI). Our findings showed that SNI significantly increased the judged quality of explanations for both conditions with the effect being more prominent for circular explanations. On the other hand, SPI had no effect on good explanations but enhanced the judged quality of circular explanations in a level comparable to that of SNI. For the first time, the SANE effect was replicated among medical students and provided preliminary data in favor of a similar effect for psychoanalytically oriented information. © 2022 Informa UK Limited, trading as Taylor & Francis Group.
Keywords: allure effect; judgment; medical training; Neuroscience; psychiatry; psychoanalysis; scientific reasoning